Low-layer inverse opal structure tin dioxide electron transport layer, preparation method and application
By using a low-layer inverse opal structure tin dioxide electron transport layer in perovskite solar cells, the loss of light absorption characteristics caused by excessive electron transport layer is solved, the photoelectric conversion rate and device stability are improved, and the Efficient utilization of perovskite materials.
Patent Information
- Application Number
- CN202310031897.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-10
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-01-10
AI Technical Summary
The excessive number of electron transport layers in existing perovskite solar cells leads to the loss of absorption characteristics of photonic crystals, affects the photoelectric conversion efficiency of perovskite materials, and reduces the electron hole separation rate and short-circuit current.
Using the preparation method of low-layer inverse opal structure tin dioxide electron transport layer, a dense tin dioxide film and close packing are formed by spin coating and drying treatment. The array of steel sphere shells controls structural size and number of layers, enhancing light absorption and electron transport.
The contact area between the electron transport layer and the perovskite layer is significantly increased, the transmission of photogenerated electrons is improved, the photoelectric conversion rate is improved, and the service life is extended while ensuring device stability and low cost.
Smart Images

Figure CN116119708B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite solar cells, and in particular relates to a low-layer (single-layer or double-layer) inverse opal structure tin dioxide electron transport layer applied to a perovskite solar cell and a preparation method thereof. Background Art
[0002] The global fossil energy crisis is increasingly threatening human survival and development. How to use environmentally friendly, clean and sustainable new energy has become a research hotspot for scientists from all over the world. Perovskite solar cells are a promising research direction due to their low cost, easy preparation and high photoelectric conversion efficiency. In recent years, perovskite solar cells have achieved rapid development, with breakthroughs in material preparation and optoelectronic device performance. Due to the wide absorption spectrum, high absorption coefficient, small exciton binding energy, balanced electron / hole mobility, benign defects and long charge carrier lifetime of perovskite materials, the photoelectric conversion efficiency of perovskite solar cells has been significantly improved, making it the most promising device in the field of photovoltaic power generation.
[0003] The electron transport layer is an important component of perovskite solar cells. Its function is to form electron-selective contact with the perovskite light absorption layer. The ideal electron transport layer needs to match the energy level of the perovskite material to reduce energy loss and promote the injection of photogenerated electrons. It should also have a high electron mobility to ensure the rapid transmission of electrons and inhibit the recombination of electrons and holes. SnO2 is a wide bandgap semiconductor, which is more compatible with the energy level of the perovskite phase and has a higher electron mobility (240cm 2 / (V·s)), which is beneficial to shorten the transmission time of electrons in the perovskite film and inhibit the recombination of electron-hole pairs. Compared with TiO2 or other ETL materials, SnO2 has excellent chemical stability, UV resistance and anti-reflection, and lower photocatalytic activity. These excellent properties are beneficial to improving the stability of the device and extending its service life.
[0004] The photonic crystal structure is used as a framework material to load semiconductor light-absorbing materials and as an electron transport layer. It has a high specific surface area and controllability of light, which can enhance the light absorption of perovskites and transport photogenerated electrons. As one of the most mature photonic crystal forming methods, the self-assembly stacking process generally has too many layers, usually more than 10 layers. And due to the compression and distortion of the stacking of opal units, some of the absorption characteristics of the photonic crystal are lost; on the other hand, for perovskites with high absorption coefficients applied to solar cell structures, the thickness of the photonic crystal only needs to be 600nm to 1000nm to fully absorb the energy of the solar light spectrum. If its thickness is too high, the sunlight cannot fully penetrate the perovskite, resulting in the perovskite cannot be fully utilized. At the same time, too thick an electron transport layer also brings greater series resistance, and reduces the electron-hole separation rate and short-circuit current of the battery. Regarding the method of simply controlling the thickness of the photonic crystal by reducing the concentration of the microsphere dispersion, because the concentration of the microspheres is too low, the meniscus of the dispersion is pinched off during the self-assembly process, and it is easy to obtain a photonic crystal with uneven number of layers, thus affecting the quality of the perovskite film. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the first object of the present invention is to provide a method for preparing a low-layer inverse opal structure tin dioxide electron transport layer, the second object is to provide a low-layer inverse opal structure tin dioxide electron transport layer prepared by the above-mentioned preparation method, and the third object is to provide the application of the above-mentioned low-layer inverse opal structure tin dioxide electron transport layer in perovskite solar cells. The low-layer inverse opal structure tin dioxide electron transport layer of the present invention, while ensuring that the electron transport layer and the perovskite layer have a large contact surface, enhances light absorption through an inverse opal structure with controllable size, controllable number of layers and a smooth surface, and makes full use of the characteristics of the high absorption coefficient of the perovskite material and the dual functionality of the photonic crystal load structure as the electron transport layer, thereby achieving the effect of improving the photoelectric conversion rate.
[0006] To achieve the above object, the specific scheme adopted by the present invention is:
[0007] In a first aspect, a method for preparing a tin dioxide electron transport layer with a low number of layers of an inverse opal structure comprises the following steps:
[0008] S1. dissolving stannous chloride dihydrate crystals in isopropanol and aging at room temperature to obtain a stannous chloride colloidal solution;
[0009] S2. Deionized water and styrene monomer were added to a three-necked flask and heated in a water bath with stirring, and nitrogen was continuously introduced, and then potassium persulfate as an initiator was added and reacted for 12 hours to obtain a polystyrene colloidal microsphere solution;
[0010] S3. The polystyrene colloidal microsphere solution obtained in step S2 is dispersed in an ethanol dispersion and ultrasonically treated to obtain a monodisperse polystyrene colloidal microsphere dispersion;
[0011] S4. The FTO conductive glass is sequentially added to acetone, deionized water and anhydrous ethanol for ultrasonic cleaning, and the clean FTO conductive glass is placed in a plasma surface treatment machine for treatment;
[0012] S5. Spin-coating the stannous chloride colloidal solution obtained in step S1 on the FTO conductive glass and annealing to obtain a glass substrate covered with a tin dioxide film;
[0013] S6. The glass substrate obtained in step S5 is sequentially added to isopropanol, deionized water and anhydrous ethanol for ultrasonic treatment;
[0014] S7. The glass substrate obtained in step S6 is vertically placed against the wall of the sample bottle, the monodisperse polystyrene colloidal microsphere dispersion obtained in step S3 is added until the entire glass substrate is submerged, a surfactant, sodium dodecyl sulfate, is added dropwise, and then the glass substrate is placed in a blast drying oven for drying to obtain a glass substrate covered with polystyrene colloidal microsphere photonic crystals;
[0015] S8. The stannous chloride colloidal solution obtained in step S1 is filled between the polystyrene colloidal microspheres on the glass substrate obtained in step S7 by spin coating and dried, and then placed in a muffle furnace for annealing and removal of the polystyrene colloidal microspheres. At the same time, tin dioxide is crystallized from the precursor solution to obtain a low-layer inverse opal structure tin dioxide electron transport layer.
[0016] Preferably, in step S1, the mass volume ratio of the stannous chloride dihydrate crystals to isopropanol is 0.576 g:25 ml; and the aging time is 96 h.
[0017] Preferably, in step S2, the volume ratio of deionized water to styrene monomer is 135 ml: (10-15) ml; the heating temperature is 90° C., the stirring speed is 300 rpm; and the mass of the initiator potassium persulfate is 0.1 g.
[0018] Preferably, the ethanol dispersion in step S3 is composed of anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is 48ml:2ml; the volume ratio of the polystyrene colloidal microsphere solution to the ethanol dispersion is 1ml:50ml; and the ultrasonic time is 10 to 30min.
[0019] Preferably, the size of the FTO conductive glass in step S4 is 20 mm*10 mm*2 mm; the time ratio of ultrasonic treatment with acetone, deionized water and anhydrous ethanol is 30 min:30 min:30 min; and the plasma surface treatment time is 450 s.
[0020] Preferably, in step S5, the stannous chloride colloidal solution is 50 μl; the spin coating speed is 3000 rpm, the spin coating time is 30 s; and the annealing temperature is 120-180°C.
[0021] Preferably, in step S6, the time ratio of the ultrasonic treatment of isopropanol, deionized water and anhydrous ethanol is 30 min:10 min:10 min.
[0022] Preferably, in step S7, the size of the sample bottle is Φ22.5mm*75mm; the tin dioxide surface of the glass substrate faces the center of the bottle; the mass of sodium dodecyl sulfate is 50-100mg; the temperature of the blast drying oven is 60°C, and the drying time is 12h.
[0023] Preferably, in step S8, the stannous chloride colloidal solution is 30 μl; the spin coating speed is 2000-3000 rpm, and the spin coating time is 60 s; the muffle furnace heating rate is 1°C / min, the first stage annealing temperature is 80-100°C, the holding time is 90 min, the second stage annealing temperature is 480-500°C, and the holding time is 120 min.
[0024] In the second aspect, a low-layer inverse opal structure tin dioxide electron transport layer is prepared by the above preparation method.
[0025] Thirdly, the application of the above-mentioned low-layer inverse opal structure tin dioxide electron transport layer in perovskite solar cells.
[0026] The advantages of the method of the present invention are as follows:
[0027] (1) The present invention significantly increases the contact area between the electron transport layer and the perovskite layer by designing an electron transport layer with an inverse opal structure, thereby improving the transmission of photogenerated electrons.
[0028] (2) The electron transport layer material in the present invention is tin dioxide photonic crystal. The structure size of the photonic crystal is controllable, the number of layers is controllable, and the surface is smooth and flat. It has good light transmittance and can enhance the effective collection of sunlight.
[0029] (3) The present invention does not require expensive equipment and raw materials during the preparation process, the experimental method is easy to operate, the experimental process is pollution-free, and the temperature and time in the experiment are relatively easy to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a cross-sectional SEM photograph of the polystyrene colloidal microsphere photonic crystal prepared in Example 1 observed under a scanning electron microscope.
[0031] Figure 2This is a cross-sectional SEM photograph of the polystyrene colloidal microsphere photonic crystal prepared in Example 4 observed under a scanning electron microscope.
[0032] Figure 3 This is a surface SEM photograph of the low-layer inverse opal structure tin dioxide electron transport layer prepared in Example 1 observed under a scanning electron microscope.
[0033] Figure 4 This is a cross-sectional SEM photograph of the low-layer inverse opal structure tin dioxide electron transport layer prepared in Example 1 observed under a scanning electron microscope.
[0034] Figure 5 It is a comparison diagram of the current density and voltage (JV) characteristic curves of perovskite solar cells prepared using the planar structure and the inverse opal structure tin dioxide electron transport layer described in the present application. DETAILED DESCRIPTION
[0035] The present invention provides a low-layer (single or double layer) inverse opal structure tin dioxide electron transport layer applied to perovskite solar cells, the structure of which is a dense tin dioxide film and a densely packed tin dioxide spherical shell array sequentially covered on a substrate. The substrate is FTO conductive glass, the thickness of the tin dioxide film is 400-500nm, the diameter of the tin dioxide spherical shell is 200-400nm, and the thickness of the spherical shell is 200-600nm. The method is to first spin-coat a stannous chloride colloidal solution on a substrate and anneal to obtain a tin dioxide film, then vertically immerse it in a polystyrene dispersion liquid to which a surfactant sodium dodecyl sulfate is added, dry it to obtain a low-layer polystyrene microsphere photonic crystal, then fill the stannous chloride colloidal solution between the colloidal microspheres by spin coating and dry it, and remove the colloidal microsphere template by calcining.
[0036] The invention has the characteristics of simple preparation process, stable process, easy operation, low cost, no pollution, etc. It has a stable and controllable structure, can be used as an electron transport layer while being applied to the framework layer of semiconductor light-absorbing materials, and as an important light-to-electric conversion structure in the perovskite solar cell device structure.
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0038] Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0039] Example 1
[0040] 1. Add 0.576 g of stannous chloride dihydrate crystals to 25 ml of isopropanol and age at room temperature for 96 hours to obtain a stannous chloride colloidal solution.
[0041] 2. Add 135 ml of deionized water and 10 ml of styrene monomer into a three-necked flask, continue to introduce nitrogen and stir at a speed of 300 rpm, heat to 90 ° C in a water bath, add 0.1 g of initiator potassium persulfate, react for 12 hours to obtain a polystyrene colloidal microsphere solution; add 2 ml of anhydrous ethanol to 48 ml of deionized water to obtain an ethanol dispersion, add 1.5 ml of the polystyrene colloidal microsphere solution to 50 ml of the ethanol dispersion, and ultrasonically treat for 30 minutes to obtain a monodisperse polystyrene colloidal microsphere dispersion.
[0042] 3. The FTO conductive glass was immersed in acetone, deionized water and anhydrous ethanol in turn for ultrasonic treatment, and the ultrasonic treatment time was 30 minutes. The clean FTO conductive glass obtained after the treatment was placed in a plasma surface treatment machine for 450 seconds.
[0043] 4. 50 μl of stannous chloride colloidal solution was dropped onto the FTO conductive glass obtained in step 3, and spin-coated at a speed of 3000 rpm for 30 seconds. After the spin coating, annealing was performed at 180° C. to obtain a glass substrate covered with a tin dioxide film;
[0044] 5. The glass substrate obtained in step 4 was immersed in isopropanol, deionized water and anhydrous ethanol in sequence for ultrasonic treatment, and the ultrasonic treatment time was 30 min, 10 min and 10 min in sequence.
[0045] 6. Place the glass substrate obtained in step 5 vertically into a sample bottle and lean it against the bottle wall, with the tin dioxide film facing the center of the bottle, add the monodisperse polystyrene colloidal microsphere dispersion into the sample bottle until the liquid level just covers the glass substrate, add 50 mg of surfactant sodium dodecyl sulfate, and then place it in a blast drying oven at 60°C for 12 hours to obtain a glass substrate covered with polystyrene colloidal microsphere photonic crystals;
[0046] 7. Add 30 μl of stannous chloride colloidal solution onto the glass substrate obtained in step 6, spin-coat at 3000 rpm for 60 s, dry at room temperature after spin coating, and then place in a muffle furnace and heat at 90°C for 90 min at a heating rate of 1°C / min, and then heat at 500°C for 120 min to calcine and remove the polystyrene colloidal microspheres to obtain a low-layer inverse opal structure tin dioxide electron transport layer.
[0047] Figure 1This is a cross-sectional SEM photograph of the polystyrene colloidal microsphere photonic crystal prepared in this example observed under a scanning electron microscope. A relatively small amount of surfactant sodium dodecyl sulfate was added dropwise to the polystyrene colloidal microsphere dispersion to obtain a double-layer polystyrene colloidal microsphere photonic crystal.
[0048] Figure 3 This is a surface SEM photograph of the low-layer inverse opal structure tin dioxide electron transport layer prepared in this embodiment observed under a scanning electron microscope. The inverse opal structure tin dioxide electron transport layer prepared on the polystyrene colloidal microsphere photonic crystal template retains the characteristic structure of the template. Compared with the electron transport layer with a planar structure, the electron transport layer with a special optical structure can enhance the absorption coefficient of the device on the one hand, and on the other hand, it can synergistically improve the efficiency of the solar cell by increasing the surface area of the electron transport layer.
[0049] Figure 4 This is a cross-sectional SEM photograph of the low-layer inverse opal structure tin dioxide electron transport layer prepared in this embodiment observed under a scanning electron microscope. The inverse opal structure tin dioxide electron transport layer prepared on the polystyrene colloidal microsphere photonic crystal template retains the number of layers of the template.
[0050] Example 2
[0051] 1. Add 0.576 g of stannous chloride dihydrate crystals to 25 ml of isopropanol and age at room temperature for 96 hours to obtain a stannous chloride colloidal solution.
[0052] 2. Add 135 ml of deionized water and 15 ml of styrene monomer into a three-necked flask, continue to introduce nitrogen and stir at 300 rpm, heat to 90 ° C in a water bath, add 0.1 g of initiator potassium persulfate, react for 12 hours to obtain a polystyrene colloidal microsphere solution; add 2 ml of anhydrous ethanol to 48 ml of deionized water to obtain an ethanol dispersion, add 1 ml of the polystyrene colloidal microsphere solution to 50 ml of the ethanol dispersion, and ultrasonically treat for 30 minutes to obtain a monodisperse polystyrene colloidal microsphere dispersion.
[0053] 3. The FTO conductive glass was immersed in acetone, deionized water and anhydrous ethanol in turn for ultrasonic treatment, and the ultrasonic treatment time was 30 minutes. The clean FTO conductive glass obtained after the treatment was placed in a plasma surface treatment machine for 450 seconds.
[0054] 4. Add 50 μl of stannous chloride colloidal solution onto the FTO conductive glass obtained in step 3, spin-coat at 3000 rpm for 30 seconds, and anneal at 180° C. after the spin coating to obtain a glass substrate covered with a tin dioxide film.
[0055] 5. The glass substrate obtained in step 4 was immersed in isopropanol, deionized water and anhydrous ethanol in sequence for ultrasonic treatment, and the ultrasonic treatment time was 30 min, 10 min and 10 min in sequence.
[0056] 6. Place the glass substrate obtained in step 5 vertically into a sample bottle and lean it against the bottle wall with the tin dioxide film facing the center of the bottle. Add the monodisperse polystyrene colloidal microsphere dispersion into the sample bottle until the liquid level just submerges the glass substrate. Add 50 mg of surfactant sodium dodecyl sulfate, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a glass substrate covered with polystyrene colloidal microsphere photonic crystals.
[0057] 7. Add 30 μl of stannous chloride colloidal solution onto the glass substrate obtained in step 6, spin-coat at 3000 rpm for 60 s, dry at room temperature after spin coating, and then place in a muffle furnace and heat at 90°C for 90 min at a heating rate of 1°C / min, and then heat at 500°C for 120 min to calcine and remove the polystyrene colloidal microspheres to obtain a low-layer inverse opal structure tin dioxide electron transport layer.
[0058] Example 3
[0059] 1. Add 0.576 g of stannous chloride dihydrate crystals to 25 ml of isopropanol and age at room temperature for 96 hours to obtain a stannous chloride colloidal solution.
[0060] 2. Add 135 ml of deionized water and 8 ml of styrene monomer into a three-necked flask, continue to introduce nitrogen and stir at 300 rpm, heat to 90 ° C in a water bath, add 0.1 g of initiator potassium persulfate, react for 12 hours to obtain a polystyrene colloidal microsphere solution; add 2 ml of anhydrous ethanol to 48 ml of deionized water to obtain an ethanol dispersion, add 1 ml of the polystyrene colloidal microsphere solution to 50 ml of the ethanol dispersion, and ultrasonically treat for 30 minutes to obtain a monodisperse polystyrene colloidal microsphere dispersion.
[0061] 3. The FTO conductive glass was immersed in acetone, deionized water and anhydrous ethanol in turn for ultrasonic treatment, and the ultrasonic treatment time was 30 minutes. The clean FTO conductive glass obtained after the treatment was placed in a plasma surface treatment machine for 450 seconds.
[0062] 4. Add 50 μl of stannous chloride colloidal solution onto the FTO conductive glass obtained in step 3, spin-coat at 3000 rpm for 30 seconds, and anneal at 180° C. after the spin coating to obtain a glass substrate covered with a tin dioxide film.
[0063] 5. The glass substrate obtained in step 4 was immersed in isopropanol, deionized water and anhydrous ethanol in sequence for ultrasonic treatment, and the ultrasonic treatment time was 30 min, 10 min and 10 min in sequence.
[0064] 6. Place the glass substrate obtained in step 5 vertically into a sample bottle and lean it against the bottle wall with the tin dioxide film facing the center of the bottle. Add the monodisperse polystyrene colloidal microsphere dispersion into the sample bottle until the liquid level just submerges the glass substrate. Add 50 mg of surfactant sodium dodecyl sulfate, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a glass substrate covered with polystyrene colloidal microsphere photonic crystals.
[0065] 7. Add 30 μl of stannous chloride colloidal solution onto the glass substrate obtained in step 6, spin-coat at 3000 rpm for 60 s, dry at room temperature after spin coating, and then place in a muffle furnace and heat at 90°C for 90 min at a heating rate of 1°C / min, and then heat at 500°C for 120 min to calcine and remove the polystyrene colloidal microspheres to obtain a low-layer inverse opal structure tin dioxide electron transport layer.
[0066] Example 4
[0067] 1. Add 0.576 g of stannous chloride dihydrate crystals to 25 ml of isopropanol and age at room temperature for 96 hours to obtain a stannous chloride colloidal solution.
[0068] 2. Add 135 ml of deionized water and 10 ml of styrene monomer into a three-necked flask, continue to introduce nitrogen and stir at 300 rpm, heat to 90 ° C in a water bath, add 0.1 g of initiator potassium persulfate, react for 12 hours to obtain a polystyrene colloidal microsphere solution; add 2 ml of anhydrous ethanol to 48 ml of deionized water to obtain an ethanol dispersion, add 1 ml of the polystyrene colloidal microsphere solution to 50 ml of the ethanol dispersion, and ultrasonically treat for 30 minutes to obtain a monodisperse polystyrene colloidal microsphere dispersion.
[0069] 3. The FTO conductive glass was immersed in acetone, deionized water and anhydrous ethanol in turn for ultrasonic treatment, and the ultrasonic treatment time was 30 minutes. The clean FTO conductive glass obtained after the treatment was placed in a plasma surface treatment machine for 450 seconds.
[0070] 4. Add 50 μl of stannous chloride colloidal solution onto the FTO conductive glass obtained in step 3, spin-coat at 3000 rpm for 30 seconds, and anneal at 180° C. after the spin coating to obtain a glass substrate covered with a tin dioxide film.
[0071] 5. The glass substrate obtained in step 4 was immersed in isopropanol, deionized water and anhydrous ethanol in sequence for ultrasonic treatment, and the ultrasonic treatment time was 30 min, 10 min and 10 min in sequence.
[0072] 6. Place the glass substrate obtained in step 5 vertically into a sample bottle and lean it against the bottle wall with the tin dioxide film facing the center of the bottle. Add the monodisperse polystyrene colloidal microsphere dispersion into the sample bottle until the liquid level just submerges the glass substrate. Add 100 mg of surfactant sodium dodecyl sulfate, and then place it in a forced air drying oven at 60°C for 12 hours to obtain a glass substrate covered with polystyrene colloidal microsphere photonic crystals.
[0073] 7. Add 30 μl of stannous chloride colloidal solution onto the glass substrate obtained in step 6, spin-coat at 3000 rpm for 60 s, dry at room temperature after spin coating, and then place in a muffle furnace and heat at 90°C for 90 min at a heating rate of 1°C / min, and then heat at 500°C for 120 min to calcine and remove the polystyrene colloidal microspheres to obtain a low-layer inverse opal structure tin dioxide electron transport layer.
[0074] Figure 2 This is a cross-sectional SEM photograph of the polystyrene colloidal microsphere photonic crystal prepared in this example observed under a scanning electron microscope. A relatively large amount of surfactant sodium dodecyl sulfate was added dropwise to the polystyrene colloidal microsphere dispersion to obtain a single-layer polystyrene colloidal microsphere photonic crystal.
[0075] Figure 5 It is a comparison diagram of the current density and voltage (JV) characteristic curves of perovskite solar cells prepared using a planar structure and an inverse opal structure tin dioxide electron transport layer as described in the present application. It can be seen from the figure that the open circuit voltage and short circuit current of the latter are higher than those of the former.
[0076] It should be noted that the above-described embodiments should be understood as illustrative rather than limiting the scope of protection of the present invention, and the scope of protection of the present invention shall be subject to the claims. For those skilled in the art, some non-essential improvements and adjustments made to the present invention still fall within the scope of protection of the present invention without departing from the essence and scope of the present invention.
Claims
1. A method for preparing a tin dioxide electron transport layer with a low number of layers of inverse opal structure, characterized in that: The steps include: S1. dissolving stannous chloride dihydrate crystals in isopropanol and aging at room temperature to obtain a stannous chloride colloidal solution; S2. Deionized water and styrene monomer were added to a three-necked flask and heated in a water bath with stirring, and nitrogen was continuously introduced, and then potassium persulfate as an initiator was added and reacted for 12 hours to obtain a polystyrene colloidal microsphere solution; S3. The polystyrene colloidal microsphere solution obtained in step S2 is dispersed in an ethanol dispersion and ultrasonically treated to obtain a monodisperse polystyrene colloidal microsphere dispersion; S4. The FTO conductive glass is sequentially added to acetone, deionized water and anhydrous ethanol for ultrasonic cleaning, and the clean FTO conductive glass is placed in a plasma surface treatment machine for treatment; S5. Spin-coating the stannous chloride colloidal solution obtained in step S1 on the FTO conductive glass and annealing to obtain a glass substrate covered with a tin dioxide film; S6. The glass substrate obtained in step S5 is sequentially added to isopropanol, deionized water and anhydrous ethanol for ultrasonic treatment; S7. The glass substrate obtained in step S6 is vertically placed against the wall of the sample bottle, the monodisperse polystyrene colloidal microsphere dispersion obtained in step S3 is added until the entire glass substrate is submerged, a surfactant, sodium dodecyl sulfate, is added dropwise, and then the glass substrate is placed in a blast drying oven for drying to obtain a glass substrate covered with polystyrene colloidal microsphere photonic crystals; S8. The stannous chloride colloidal solution obtained in step S1 is filled between the polystyrene colloidal microspheres on the glass substrate obtained in step S7 by spin coating and dried, and then placed in a muffle furnace for annealing and removal of the polystyrene colloidal microspheres. At the same time, tin dioxide is crystallized from the precursor solution to obtain a low-layer inverse opal structure tin dioxide electron transport layer.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass volume ratio of the stannous chloride dihydrate crystals to isopropanol is 0.576 g:25 ml; and the aging time is 96 h.
3. The preparation method according to claim 1, characterized in that: In step S2, the volume ratio of deionized water to styrene monomer is 135 ml: (10-15) ml; the heating temperature is 90° C., the stirring speed is 300 rpm; and the mass of the initiator potassium persulfate is 0.1 g.
4. The preparation method according to claim 1, characterized in that: In step S3, the ethanol dispersion consists of anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is 48ml:2ml; the volume ratio of the polystyrene colloidal microsphere solution to the ethanol dispersion is 1ml:50ml; and the ultrasonic time is 10 to 30min.
5. The preparation method according to claim 1, characterized in that: In step S4, the size of the FTO conductive glass is 20 mm*10 mm*2 mm; the time ratio of ultrasonic treatment of acetone, deionized water and anhydrous ethanol is 30 min:30 min:30 min; and the plasma surface treatment time is 450 s.
6. The preparation method according to claim 1, characterized in that: In step S5, the stannous chloride colloidal solution is 50 μl; the spin coating speed is 3000 rpm, and the spin coating time is 30 s; the annealing temperature is 120-180° C.; in step S6, the time ratio of the isopropanol, deionized water and anhydrous ethanol ultrasonic treatment is 30 min:10 min:10 min.
7. The preparation method according to claim 1, characterized in that: In step S7, the size of the sample bottle is Φ22.5mm*75mm; the tin dioxide surface of the glass substrate faces the center of the bottle; the mass of sodium dodecyl sulfate is 50-100mg; the temperature of the blast drying oven is 60°C, and the drying time is 12h.
8. The preparation method according to claim 1, characterized in that: In step S8, the stannous chloride colloidal solution is 30 μl; the spin coating speed is 2000-3000 rpm, and the spin coating time is 60 s; the muffle furnace heating rate is 1°C / min, the first stage annealing temperature is 80-100°C, the holding time is 90 min, the second stage annealing temperature is 480-500°C, and the holding time is 120 min.
9. A tin dioxide electron transport layer with a low number of layers and an inverse opal structure prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the low-layer inverse opal structure tin dioxide electron transport layer according to claim 9 in perovskite solar cells.
